Service quality and institutional image as predictors of customer satisfaction in municipalities of Perú - Mori Rojas, Gina (2023)
Objective: This research aimed to analyse the predictability of service quality and institutional image for customer satisfaction in municipalities in Peru. Theoretical framework: In this sense, one of the most important links between differentiation of services that can only be recognised and appreciated by the customer and competitive advantages or institutional image has become essential parts of organisations; it is the quality of services provided by public organisations such as municipalities that are under scrutiny and subject to evaluation and satisfaction of their users.Methodology:It was based on a quantitative, prospective correlational approach, with a sample of 352 users of municipalities in Peru. Results:An R2 of 0.460 was obtained, and the effect size was calculated with a coefficient of 0.851, which is considered a very high parameter above 0.350. The calculation of the significant statistical power resulted in a value of 1, which is considered very high. Furthermore, the standardisation coefficients have shown that service quality and institutional image are relevant, positive and significant predictors of customer satisfaction in Peruvian municipalities. Additionally, service quality was found to be the predominant predictor (beta=0.654).Conclusion:This study showed that there is a relationship between users' perceptions of service quality and institutional image and its predictive correspondence on their satisfaction. Citizens' satisfaction with theservices provided by Peruvian municipalities was influenced to a greater extent by the public image of the entities.